ANALYSIS OF CONSUMPTION PATTERNS OF MILLENNIAL MUSLIM ENTREPRENEURS USING E-WALLETS IN THE DIGITAL ERA - AYU ARISKA; SYAHRAENI SYAHRAENI; OTONG KARYPONO (Universitas Islam Darul 'ulum Lamongan, 2025)
This study aims to explore the impact of E-wallet technology on the consumption patterns of millennial Muslim entrepreneurs in Bone Regency after using E-wallets in the digital era. The research method employed is field research using a qualitative approach, with observation and interviews as data collection techniques. The study identifies consumption patterns concerning primary, secondary, and tertiary needs among millennial Muslim entrepreneurs. The findings indicate that millennial Muslim entrepreneurs in Bone Regency exhibit adaptive consumption patterns in response to E-wallet adoption, prioritizing essential needs over desires, which aligns with Islamic consumption principles. This digital transformation significantly affects their habits, making E-wallets the primary payment method and changing how they meet primary needs such as food and clothing, as well as secondary needs like transportation and business capital. E-wallets also influence their spending patterns, increasing out-of-home activities and contributing to tertiary needs such as vacations and shopping through promotions and cashback. The research shows that E-wallet adoption not only creates a more efficient consumption pattern but also positively impacts business growth, fosters a technology-responsive environment, and encourages changes in consumption behavior that align with contemporary developments while upholding Islamic values.